1993
DOI: 10.1128/jcm.31.9.2446-2450.1993
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale DNA fingerprinting of Mycobacterium tuberculosis strains as a tool for epidemiological studies of tuberculosis

Abstract: We conducted a large-scale DNA fingerprinting analysis of Mycobacterium tuberculosis strains in a country in which tuberculosis is endemic (Tunisia) in order to evaluate the importance of microepidemics in the maintenance of the disease within the population. The genetic polymorphisms of 201 strains of M. tuberculosis isolated from 196 unrelated patients living in four districts of northern Tunisia during a 3-year period were studied by restriction fragment length polymorphism (RFLP) analysis by using the inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
17
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(24 citation statements)
references
References 14 publications
5
17
1
Order By: Relevance
“…By use of IS6110 DNA fingerprinting the degree of DNA polymorphism of M. tuberculosis strains isolated in Dar es Salaam was found to be similar to that recently observed in New York and San Francisco (1,23) because the average number of isolates per pattern was 1.33 for the present study, whereas for the study in New York it was 1.35 and for the study in San Francisco it was 1.5. It might be expected that regions suffering from a high level of TB transmission and insufficient In contrast to recent observations from a large-scale RFLP study of M. tuberculosis isolates in Tunisia (6) and an ongoing study in Denmark (31), the number of IS6110 copies observed in the isolates investigated in the present study was rather evenly distributed within a range of from 1 to 20. In the study in Tunisia, about 75% of the investigated isolates of M. tuberculosis were found to carry from 6 to 10 copies of the IS6110 element.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…By use of IS6110 DNA fingerprinting the degree of DNA polymorphism of M. tuberculosis strains isolated in Dar es Salaam was found to be similar to that recently observed in New York and San Francisco (1,23) because the average number of isolates per pattern was 1.33 for the present study, whereas for the study in New York it was 1.35 and for the study in San Francisco it was 1.5. It might be expected that regions suffering from a high level of TB transmission and insufficient In contrast to recent observations from a large-scale RFLP study of M. tuberculosis isolates in Tunisia (6) and an ongoing study in Denmark (31), the number of IS6110 copies observed in the isolates investigated in the present study was rather evenly distributed within a range of from 1 to 20. In the study in Tunisia, about 75% of the investigated isolates of M. tuberculosis were found to carry from 6 to 10 copies of the IS6110 element.…”
Section: Discussioncontrasting
confidence: 99%
“…The low rate of primary drug resistance observed in the present study showed that, despite the substantial difficulties in Tanzania, as in all other developing countries, the national TB control program in Tanzania has proved to be quite efficient. In accordance with previous findings (6,26), there was no correlation between DNA fingerprint patterns and drug resistance. However, phenotypic characteristics which classify M. tuberculosis strains as being of the Asian subgroup correlated with a low IS6110 copy number per isolate.…”
Section: Discussionsupporting
confidence: 92%
“…In this cohort analysis we have found a large degree of IS6110 polymorphisms among the strains. The number of copies ranged from 1 to 16 elements (1 to 6 copies in 19.2% of the isolates, 7 to 11 copies in 65.4% of the isolates, and 12 to 16 in 15.4% of the isolates), similar to what has been reported previously (6,33). All strains had been identified as M. tuberculosis, including two (isolates 19 and 20) exhibiting only a single copy of IS6110 (verified by their strongly positive nitrate and niacin reactions, the aerophilic growth characteristics on Lebek medium, and their resistance to thiophene-2-carboxylic acid hydrazide which thus rules out their identity as Mycobacterium bovis [15]).…”
Section: Discussionsupporting
confidence: 86%
“…Restriction fragment length polymorphism (RFLP) typing of Mycobacterium tuberculosis has become a powerful tool for differentiating strains with a high degree of confidentiality and circumvents the significant limitations of other systems which are based on phages or antibiotic susceptibility patterns (6,31). The level of genetic relatedness of M. tuberculosis strains can easily be visualized by probing chromosomal DNA of tubercle bacilli with genetic markers which result in distinct RFLP patterns.…”
mentioning
confidence: 99%
“…Molecular clusters defined by the applied genotyping methods are a surrogate marker for recent transmission and epidemiological linked cases [23]. The high clustering rate of 63.8% in this study indeed indicates that the majority of active TB cases in Eastern Ethiopia are due to recent transmission and not reactivation.…”
Section: Discussionmentioning
confidence: 70%